Diversidad estructura y concentración de carbono en un bosque siempre verde piemontano de 800 a 900 m s. n. m. en la Amazonia Ecuatoriana. - Zambrano Palma, Jeanine Valeria (2020)
This research project was carried out with the objective of analyzing the diversity, structure, and concentration of carbon in an evergreen piemontan forest of the Center for Postgraduate Research and Amazon Conservation "CIPCA", of the Amazonian State University in the altitude gradient of 800-900 masl. The research was carried out in permanent sampling plots of 10 x 100 m2 between 801 and 900 masl. previously established in a study, within the framework of the Project "Biodiversity and Carbon in the Piatúa River Basin", Through the data obtained, the existence of a total of 322 individuals of trees with DBH ≥ 10 cm was determined, forming 37 families and 85 species: with a basal area of 16.17 m2 and a volume of 256.74 m3 . At a general level, the family with the highest species diversity is Moraceae with 19 species representing 22.35% of the total. The family and specie with the highest IVI value were Moraceae (12.84%) and Iriartea deltoidea (9.59%) respectively. For the analysis of the horizontal and vertical structure, the DBH and diameter data of the projection of the tree canopy will be considered, using ArcGis v 10.2.2. It has been made the graph of the horizontal and vertical profiles. The accumulated aerial biomass (AGB) by the species in the altitudinal gradient is reflected in a total average of 157.91 Mg ha-1 , a value that projects an accumulation of carbon per hectare reflects a total of 1579.05 Mg ha-1 . The species with the highest accumulation of aerial biomass is Ficus cuatracasana Dugand, with only one individual registered an AGB of 230.02 Mg ha-1 . Keywords: diversity, structure, carbon concentration